142k views
1 vote
C) 4−4/5= 2

d) –4 + 3 ( 2 – x) = –8

e) 8 – ( 5 – 9x ) = 7( 1 – x )

f) –5 – 3( x + 1 ) = –( –4x + 1)

g) 4−6/9= 1/3+ x

Powodzenia ☺​

1 Answer

5 votes

Explanation:

I will skip question c as there is no subject to solve.

d)


- 4 + 3(2 - x) = - 8 \\ - 4 + 6 - 3x = - 8 \\ 2 - 3x = - 8 \\ - 3x = - 8 - 2 \\ - 3x = - 10 \\ x = 10 / 3 \\ = (10)/(3) \: or3 (1)/(3)

e)


8 - (5 - 9x) = 7(1 - x) \\ 8 - 5 + 9x = 7 - 7x \\ 3 + 9x = 7 - 7x \\ 3 + 9x + 7x = 7 \\ 16x = 7 - 3 \\ 16x = 4 \\ x = 4 / 16 \\ = (1)/(4)


- 5 - 3(x + 1) = - ( - 4x + 1) \\ - 5 - 3x - 3 = 4x - 1 \\ - 8 - 3x = 4x - 1 \\ - 8 - 3x - 4x = - 1 \\ - 7x = - 1 + 8 \\ - 7x = 7 \\ x = 7 / - 7 \\ = - 1

g)


4 - (6)/(9) = (1)/(3) + x \\ 4 - (2)/(3) = (1)/(3) + x \\ x + (1)/(3) = 4 - (2)/(3) \\ x = 4 - (2)/(3) - (1)/(3) \\ = 4 - 1 \\ = 3

User Hativ
by
4.8k points